Pengaruh Pendidikan Jasmani Bagi Anak Sekolah Dasar untuk Pembentukan Karakter di Era Modern - Fajar Siddik; Alya Sania Putri; Aulia Dea Ananda; Iasyah Fakhrany; Munisa Putri (Universitas Palan, 2024)
This research aims to examine the influence of physical education for elementary school children on character formation in the modern era. By using the literature review method, which begins with identifying relevant sources. The results of the research show that physical education in the modern era has a very important role in development. holistic children. Physical education does not only focus on physical aspects, but also includes cognitive, effective and psychomotor development. Physical education contributes to the formation of students' character and social skills in the modern era. In this context, the role of teachers as role models is crucial, where they are expected to deliver materials in creative and interactive ways, including utilizing digital platforms such as TikTok to attract students' interest. The research also highlights the challenges faced in implementing physical education, such as the lack of facilities and resources and the need for professional training for teachers to improve the quality of learning. Thus, physical education is expected to contribute not only to students' physical health, but also to the development of social skills and adaptability in an increasingly digitalized world.